P Pemanfaatan Waktu Jam Kosong pada Peserta Didik Kelas VII di SMPN 1 Kelumpang Tengah - Rafiqurrahman, Ahmad; Rahmadi, Rahmadi; Rakhman, Arie (Jurnal Porkes, 2024)
This study aims to examine the utilization of free time by seventh grade students at SMPN 1 Kelumpang Tengah and its impact on them. The method used was a survey method used with data collection techniques in the form of questionnaires. The population in this study were all students of SMPN 1 Kelumpang Tengah which involved 31 students of class VII as samples. The results showed that class management (empty hours) showed 100% reported that they often experienced empty hours, 68% received instructions, 32% reported often receiving instructions, student involvement in empty hours, namely most students 65% often do homework, 61% play social media on mobile phones, 55% play outside the classroom. While the impact of empty hours most students 65% often feel bored, with 71% of students often feel satisfied during empty hours, with 68% of students only sometimes motivated. Students' activities during empty hours are mostly filled with non-academic activities such as sleeping, playing games and social media, and playing outside the classroom, while academic activities such as reading textbooks are rarely done. The impact of free time varies; most students feel bored, but there are also those who feel satisfied with the free time.